Re-writing theatrical documentaries: The broadcast version. (1st June 2019) - Hart, Phoebe
In the funding matrix for major theatrical documentaries, television networks are often sought out as commissioners, particularly in territories such as Australia, where a plan in the form of distribution agreement and/or broadcaster pre-sale is required to access screen agency funds. As part of the deals with the broadcaster, there are mandated deliverables in the form of a 'broadcast version' of the documentary film, typically one hour in length or as a series. For producers, this arrangement raises much-needed production finance and capitalizes on the property's reach and earning potential by exploiting the various distribution windows available. However, these deals lead to vexatious practical concerns in re-versioning for broadcast as documentary screenwriters are challenged to make changes while attempting to maintain the tone of their work. This research delves into the creative and cognitive processes as experienced by screenwriters who must 'cut down' a theatrical version of a documentary for broadcast. The research presents three case studies drawn from in-depth interviews, which are examined via a thematic analysis methodology to understand the processes of re-writing, including changes to narration, tone, style, character and narrative arcs, and thematic treatment. The research examines what is sacrificed due to time restrictions and viewer sensibilities, and whether or not the key intentions of documentary screenwriters can be preserved.